2019
DOI: 10.47611/jsr.v7i2.426
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Rbm45/Drbp1: Genomic Structure, Expression, and Evolution

Abstract: RNA recognition motif-type RNA-binding domain containing proteins (RBDPs) participate in RNA metabolism including regulating mRNA stability, nuclear-cytoplasmic shuttling, and splicing. Rbm45 is an RBDP first cloned from rat brain and expressed spatiotemporally during rat neural development. More recently, RBM45 has been associated with pathological aggregates in the human neurological disorders amyotrophic lateral sclerosis, frontotemporal lobar degeneration, and Alzheimer’s. Rbm45 and the neural developmenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Our lab [26] has previously demonstrated that nucleotide and amino acid phylograms of 10 vertebrate Rbm45 orthologues recapitulate accepted taxonomic relationships between classes Actinopterygii (ray-finned fishes), Amphibia, Reptilia, and Mammalia; additionally, through NCBI database interrogation, we reported Rbm45 orthologues, both empirically confirmed and Gnomon algorithm predicted (https://www.ncbi.nlm.nih.gov/genome/annotation_euk/process/), across metazoan taxa including animals from the non-Bilateria phyla Porifera (sponges) and Cnidaria (e.g., hydra), and within clade Bilateria phyla from the nephrozoan lineages Protostomia (e.g., phyla Mollusca and Arthropoda) and Deuterostomia (e.g., phyla Echinodermata and Chordata). Molecular phylogenetic analysis has been successfully used to reconstruct the evolutionary history of populations, genes, and proteins; furthermore, it has been utilized to understand genome organization and gene conservation [81,82].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our lab [26] has previously demonstrated that nucleotide and amino acid phylograms of 10 vertebrate Rbm45 orthologues recapitulate accepted taxonomic relationships between classes Actinopterygii (ray-finned fishes), Amphibia, Reptilia, and Mammalia; additionally, through NCBI database interrogation, we reported Rbm45 orthologues, both empirically confirmed and Gnomon algorithm predicted (https://www.ncbi.nlm.nih.gov/genome/annotation_euk/process/), across metazoan taxa including animals from the non-Bilateria phyla Porifera (sponges) and Cnidaria (e.g., hydra), and within clade Bilateria phyla from the nephrozoan lineages Protostomia (e.g., phyla Mollusca and Arthropoda) and Deuterostomia (e.g., phyla Echinodermata and Chordata). Molecular phylogenetic analysis has been successfully used to reconstruct the evolutionary history of populations, genes, and proteins; furthermore, it has been utilized to understand genome organization and gene conservation [81,82].…”
Section: Resultsmentioning
confidence: 99%
“…NCBI gene annotation (https://www.ncbi.nlm.nih.gov/homologene/?term=Rbm45 [accessed 2024 February 4]), our previous work [26], and data from Tamada et al [27] reveal that Rbm45 contains four RBDs. However, ensuing work by two leading Rbm45 research teams show an alternative structure with three RBDs [31,32]; for consistency, we have adopted these research team’s Rbm45 domain nomenclature for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rbm45 is an ancient gene, conserved from sponges to humans [26]. The human RBM45 locus on chromosome 2q31.2 [26] encodes a promiscuous RBDP found to be expressed under normal physiological conditions predominantly in neuronal tissue of rats [27], mice [26,28], and humans [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Rbm45 is an ancient gene, conserved from sponges to humans [26]. The human RBM45 locus on chromosome 2q31.2 [26] encodes a promiscuous RBDP found to be expressed under normal physiological conditions predominantly in neuronal tissue of rats [27], mice [26,28], and humans [29,30]. Rbm45 has three canonical RNA-binding domains (RBD I, II, III) [27,31,32] that preferentially bind GC-rich RNA sequence motifs [27,33,34] and have recently been shown to facilitate binding to single-stranded DNA [35]; additionally, N-terminal RBD I and RBD II have been demonstrated to participate in RNA-independent protein-protein interactions [36].…”
Section: Introductionmentioning
confidence: 99%